Is Pediatric Intensive Care Trauma-Informed? A Review of Principles and Evidence - Lauren A. Demers; Naomi M. Wright; Avi J. Kopstick; Claire E. Niehaus; Trevor A. Hall; Cydni N. Williams; Andrew R. Riley (MDPI AG, 2022)
Pediatric critical illness and injury, along with the experience of recovering from critical illness are among the most potentially traumatic experiences for children and their families. Additionally, children often come to the Pediatric Intensive Care Unit (PICU) with pre-existing trauma that may sensitize them to PICU-related distress. Trauma-informed care (TIC) in the PICU, while under-examined, has the potential to enhance quality of care, mitigate trauma-related symptoms, encourage positive coping, and provide anticipatory guidance for the recovery process. This narrative review paper first describes the need for TIC in the PICU and then introduces the principles of TIC as outlined by the American Academy of Pediatrics: awareness, readiness, detection and assessment, management, and integration. Current clinical practices within PICU settings are reviewed according to each TIC principle. Discussion about opportunities for further development of TIC programs to improve patient care and advance knowledge is also included.